STUDY OF CHANGES IN NICKEL CONTENT FROM EXPLORATION RESULTS WITH MINING ACTIVITIES AT PT. MINERAL BINTANG DELAPAN, MOROWALI DISTRICT - Saputra, Apriadi; Alhabsyi, Gina Audina P; Bundang, Syarifullah; Botjing, Muslimin U; Lantapi, Adriansyah Wuriadin (Fakultas Teknik Universitas Khairun, 2025)
In mining activities, there is often a discrepancy between the plan and actual conditions in the field. The purpose of this study is to determine the factors causing changes in Ni levels between exploration and mining activities. This study used drill sample data and mining samples using grab sampling (assay). From the results of the study, the Ni content value in exploration activities was 1.83% and in mining activities was 1.73% with a difference in content of 0.10%. The results of the difference in content are the influence of factors such as the heterogeneous nature of nickel, drilling activities, topographic conditions, mining methods, controlling factors for dilution, waste position to ore, reserve calculation methods, rainwater and human error.